Penerapan Metode Imla’ Mandzur Pada Pembelajaran Maharah Kitabah: The Imla' Mandzur Method in Learning Maharah Kitabah - ‘Ula, Elok Milhana Rohmatul; Faruq, Umar; Sholihuddin, Ahmad (Al-Wasil, 2023)
Factors related to writing skills to improve students' abilities include the methods used by teachers. And one of the learning methods related to writing skills is the imla' mandzur method. This method can train students in measuring memory and writing Arabic.This research is a type of qualitative descriptive research and the method used in this research is a qualitative method, with the Miles and Huberman approach. Data collection methods are interviews, observation and documentation, or what is usually called the triangulation method. The formulation of the problem in this research is how to apply the imla' mandzur method and what problems are faced. The aim of the research is to find out how to apply the imla' mandzur method, what are the problems in applying the imla' mandzur method. The results of this research show that the application of the imla' mandzur method in class VIII MTs Nurul Islam can improve students' writing skills. the process of implementing the imla' mandzur method includes giving mufrodat before learning, students are asked to observe the reading text, once it is sufficient then the teacher asks students to close the reading text, the teacher dictates the text and students are asked to write what the teacher dictates on the worksheet without looking at the reading text . Sometimes the teacher also writes a reading text on the blackboard, asks the students to observe the writing, the teacher erases the writing and dictates it. The problem faced is that students do not master Arabic vocabulary, making it difficult for them to follow writing skills using the imla' mandzur method.